Palliative care in gynecologic oncology. Issue 1 (February 2018) - Karlin, Daniel; Phung, Peter; Pietras, Christopher
Abstract : Purpose of review: Patients with gynecologic malignancies face many difficult issues in the course of their diseases, ranging from physical symptoms to advance care planning in light of a poor prognosis. This review examines the evidence supporting integration of palliative care early in the course of disease and symptom management, and provides a framework for difficult conversations. Recent findings: Palliative care has been demonstrated to improve quality of life and promote survival if integrated early in the course of disease. An evidence-based approach should guide symptom management, such as pain and nausea. Advance care planning and goals of care discussions are enhanced by a framework guiding discussion and the incorporation of empathetic responses. Summary: Palliative care is a diverse multidisciplinary field that can provide significant benefit for patients with gynecologic malignancies.